Institutional and Seasonal Variations in the Incidence and Causative Organisms for Posttraumatic Infection following Open Fractures. Issue 2 (February 2017) - Sagi, H. Claude; Donohue, David; Cooper, Seth; Barei, David P.; Siebler, Justin; Archdeacon, Michael T.; Sciadini, Marcus; Romeo, Michelle; Bergin, Patrick F.; Higgins, Thomas; Mir, Hassan; ,
Abstract : Supplemental Digital Content is Available in the Text. Abstract : Objectives: The current literature focuses on wound severity, time to debridement, and antibiotic administration with respect to risk of infection after open fracture. The purpose of this analysis was to determine if either the incidence of posttraumatic infection or causative organism varies with treating institution or the season in which the open fracture occurred. Design: Retrospective review. Setting: Seven level 1 regional referral trauma centers located in each of the 7 climatic regions of the continental United States (Northwest, High Plains, Midwest/Ohio Valley, New England/Mid-Atlantic, Southeast, South, and Southwest). Patients/Participants: Five thousand one hundred twenty-seven skeletally mature patients with open extremity fractures treated between 2008 and 2012 at one of the 7 institutions. Intervention: Open reduction and internal fixation of fracture following institutional protocol for antibiotic prophylaxis, debridement, and soft-tissue management. Main Outcome Measurements: Seasonal variation on the incidence of infection and the causative organism after treatment for open fracture as recorded by each individual treating institution. Charts were analyzed to extract information regarding date of injury, Gustilo–Anderson type of open fracture, subsequent treatment for a posttraumatic wound infection, and the causative organisms. Patients were placed into one of the 4 groups based on the time of year that the injury occurred: spring (March–May), summer (June–August), fall (September–November), and winter (December–February). Univariate/multivariate analyses and Fisher test were used to assess whether any observed differences were of statistical significance. Results: The overall incidence of infection for all open fractures across the 7 different institutions was 7.6% and this did not vary significantly by season. There were, however, significant differences in overall infection rates between the different institutions: Southeast 4.3%, Northwest 13%, Northeast 7.7%, Southwest 9.3%, Midwest/Ohio Valley 5.5%, High Plains 14.6%, and South 7.4%. The following institutions demonstrated a significant seasonal variation in the incidence of infection: Northwest = fall 11% versus winter 18.5%, Southwest = winter 1.5% and fall 17.3%, Northeast = winter 5.2% and spring 9.7%, and Southeast = fall 2.8% and spring 6.0%. The High Plains, Midwest/Ohio Valley, and Southern institutions did not demonstrate a significant seasonal variation in infection rates. Finally, the most commonly encountered causative organism varied not only by region, but by season as well. Staphylococcus aureus (both methicillin sensitive and resistant) continues to be the most prevalent organism in the continental United States. Conclusions: A substantial seasonal and institutional variation exists regarding the incidence of infection and causative organisms for posttraumatic wound infection after open fractures. Although this may represent a difference in treatment regimens between individual surgeons and institutions, a decades-old general nation-wide empiric antibiotic prophylaxis regimen for all open fractures may in fact be outdated and suboptimal. We recommend that surgeons consult with their infectious disease colleagues to better understand the seasonal variation of infection and causative organism for their individual hospital, and adjust their prophylactic and treatment regimens accordingly. Level of Evidence: Prognostic Level III. See Instructions for Authors for a complete description of levels of evidence.